Interhemispheric Functional Brain Connectivity in Neonates with Prenatal Alcohol Exposure: Preliminary Findings. (January 2016) - Donald, Kirsten A.; Ipser, Jonathan C.; Howells, Fleur M.; Roos, Annerine; Fouche, Jean‐Paul; Riley, Edward P.; Koen, Nastassja; Woods, Roger P.; Biswal, Bharat; Zar, Heather J.; Narr, Katherine L.; Stein, Dan J.
Abstract : Background: Children exposed to alcohol in utero demonstrate reduced white matter microstructural integrity. While early evidence suggests altered functional brain connectivity in the lateralization of motor networks in school‐age children with prenatal alcohol exposure (PAE), the specific effects of alcohol exposure on the establishment of intrinsic connectivity in early infancy have not been explored. Methods: Sixty subjects received functional imaging at 2 to 4 weeks of age for 6 to 8 minutes during quiet natural sleep. Thirteen alcohol‐exposed (PAE) and 14 age‐matched control (CTRL) participants with usable data were included in a multivariate model of connectivity between sensorimotor intrinsic functional connectivity networks. Seed‐based analyses of group differences in interhemispheric connectivity of intrinsic motor networks were also conducted. The Dubowitz neurological assessment was performed at the imaging visit. Results: Alcohol exposure was associated with significant increases in connectivity between somatosensory, motor networks, brainstem/thalamic, and striatal intrinsic networks. Reductions in interhemispheric connectivity of motor and somatosensory networks did not reach significance. Conclusions: Although results are preliminary, findings suggest PAE may disrupt the temporal coherence in blood oxygenation utilization in intrinsic networks underlying motor performance in newborn infants. Studies that employ longitudinal designs to investigate the effects of in utero alcohol exposure on the evolving resting‐state networks will be key in establishing the distribution and timing of connectivity disturbances already described in older children. Abstract : Prenatal alcohol exposure was associated with significant increases in connectivity in six intrinsic networks underlying motor performance in this group of neonates compared to unexposed controls. Axial, sagittal and coronal slices of ICA derived networks (shown in orange‐yellow), thresholded at Z = 4 and superimposed on the UNC neonatal template. Networks: (a) anterior motor, (b) posterior motor, (c) left somatosensory, (d) right somatosensory, (e) striatal and (f) brainstem/thalamic